Sexism issues in the Tears of the Giraffe by Alexander McCall Smith - Hussein Kadhim Zamil (Journal La Sociale, 2022)
The findings of this study are likely to add to the growing body of literature-related research, particularly on the topic of liberal sexism in literary works. Using liberal feminist literary studies, this work employs a literary strategy based on literary criticism. The book Tears of the Giraffe by Alexander McCall Smith, published by Abascus, is the subject of this study. The book Tears of the Giraffe serves as the major data source for this investigation. In 2006, this book was released with 398 pages of content. Reading, listening, and taking notes were the primary methods of gathering data for this investigation. A qualitative descriptive method was used to analyze the data. The novel's characters, locations, and themes were used to identify sexims issues in the novel's content. It may be seen in the novel's characters that women degrade other female characters in terms of sexism. Male characters don't denigrate the female character as much as they might. It may discern the shape of the sexism dilemma by looking for statements or quotations that suggest it. According to Alexander McCall Smith's book Tears of the Giraffe, women have sexism issues. For both family and business, Alexander McCall Smith portrayed in Tears of the Giraffe.